Detection and differentiation of Leishmania parasites in asymptomatic canine by High-Resolution Melting analysis of microsatellite fragment in ITS gene. (January 2022) - Najafzadeh, N.; Taslimian, R.; Fotouhi-Ardakani, R.; Spotin, A.; Parvizi, P.
Abstract: The high prevalence of Leishmania infection was reported in dogs as the main reservoir of CanL in many locations in the old world. Detection and firmly identification of Leishmania species in asymptomatic dogs by reliable method was considered and employed. Non-invasive and non-anesthetized blood sampling in asymptomatic dogs was conducted. Nested, conventional and real-time PCR with HRM technique was performed targeting ITS-rDNA gene. 88 asymptomatic dogs were sampled from three CanL endemic provinces of Iran in 2018–2019. 23 blood samples were Leishmania positive. L. major, L. tropica and L. infantum were accurately identified for the first time with HRM targeting ITS2-microsatellite. Three samples were mixed infections. CLC software TM predictions for microsatellite ITS-rDNA were 86.93 °C: L. major, 85.76 °C: L. tropica and 86.04 °C: L. infantum . Standard strains of Leishmania species were accurately separated with almost one to 2 °C deference ( L. major : 86.61 °C, L. infantum : 85.41 °C, L. tropica : 84.82 °C). Each HRM curve represents one species in a sample for helping accurate identification of Leishmania species and even mixed infection when two curves are present. Detecting parasites at primary stages in asymptomatic cases is essential using Real-time HRM. As same as mammalian Leishmania in rodents which is present at early stages and non-pathogenesis, only L. major would exist and other Leishmania disappears. This can conclude also for L. major, L. infantum and L. tropica in dogs. The role of L. major existence in canine blood should be investigated more. Graphical abstract: Image 1 Highlights: Non-invasive blood samples from asymptomatic dogs examined in endemic areas. Conventional, nested and qPCR- HRM analysis targeting ITS-rDNA gene was performed. HRM separated L.major, L. infantum & L. tropica at 86.6, 85.4 & 84.8 °C respectively. L. major L. infantum and L. tropica identified from asymptomatic canine blood. Recommending HRM for Leishmania infection in vector, human & asymptomatic reservoirs.